Review of Spectacular Modernity: Dictatorship, Space, and Visuality in Venezuela, 1948-1958, by Lisa Blackmore - Luiz Lara, Fernando (European Review of Latin American and Caribbean Studies, 2018)
Spectacular Modernity: Dictatorship, Space, and Visuality in Venezuela, 1948-1958, by Lisa Blackmore. University of Pittsburgh Press, 2017